Human genital dendritic cell heterogeneity confers differential rapid response to HIV-1 exposure - Parthasarathy, Siddharth; Moreno de Lara, Laura; Carrillo-Salinas, Francisco J.; Werner, Alexandra; Borchers, Anna; Iyer, Vidya; Vogell, Alison; Fortier, Jared M.; Wira, Charles R.; Rodriguez-Garcia, Marta (Frontiers in Immunology, 2024)
Dendritic cells (DCs) play critical roles in HIV pathogenesis and require further investigation in the female genital tract, a main portal of entry for HIV infection. Here we characterized genital DC populations at the single cell level and how DC subsets respond to HIV immediately following exposure. We found that the genital CD11c + HLA-DR + myeloid population contains three DC subsets (CD1c+ DC2s, CD14+ monocyte-derived DCs and CD14 + CD1c + DC3s) and two monocyte/macrophage populations with distinct functional and phenotypic properties during homeostasis. Following HIV exposure, the antiviral response was dominated by DCs' rapid secretory response, activation of non-classical inflammatory pathways and host restriction factors.Further, we uncovered subset-specific differences in anti-HIV responses. CD14+ DCs were the main population activated by HIV and mediated the secretory antimicrobial response, while CD1c+ DC2s activated inflammasome pathways and IFN responses. Identification of subsetspecific responses to HIV immediately after exposure could aid targeted strategies to prevent HIV infection.